A Historical Look at Cuban Cinema Today: the Image that Is Constructed (2016-2024) - Álvarez Pitaluga, Antonio (2025)
Introduction: Since 1959, Cuban cinema has become one of the most influential cinematographies of the continent. Marked by trends such as Neorealism and the New Wave, it developed an important social outlook on different national and continental issues. However, since the beginning of the 21st century, its production points in other directions that do not contribute to this referential image. Objective: The paper aims to analyze how the economic crisis, the lack of resources, the progressive emigration, and the State pressure from its cultural policies constitute some of the causes that affect this reality. Methods: Historical-logical and critical analysis methods were employed. Results: The study demonstrates that the current Cuban cinema is immersed in a production and creation crisis, as well as under certain hegemonic pressures. Conclusions: Finally, it is determined that its capacity for social gazes and aesthetic experimentation has been reduced in recent years.